A produção de material didático digital para o ensino de inglês: o desafio da transposição didática - Guimarães, Elvandir Guedes (2020)
This work, developed in the concentration area Educacional Network Technologies: Innovation and Democratization, within the research line Development of Educational Network Technologies, from PPGTer/UFSM, aims at presenting a proposal for digital didactic materials production aligned with theoretical assumptions of the National Common Curricular Base for English language teaching and learning. Methodologically supported by Design-Based Research (DBR), a diagnostic questionnaire was apllied in some schools in the city of Santa Maria, which was designed to map information related to teachers’ formation and their pedagogical practices in English Language subject. Through this, it was possible to verify the schools’ reality, the main resources used in the classroom and the interest of the teachers who participate in the research in receiving digital didatic materials developed in this work. The data obtained were taken into account during the process of Digital Didactic Materials production for sixth grade students. After that, the product was made available on a website created on Google Sites, due to the lack of didactic material detected in public schools and the social isolation in the Covid-19 Pandemic, which led to a new temporary teaching modality: Emergency Remote Teaching. The challenge of Didactic Transposition (CHEVALLARD, 1991), as well as the technological fluency development in some authoring tools, were the two biggest obstacles in this stage, as they required a lot of reflection, so that our knowledge would be adequate to the student's level/age range and lead to effective learning of our target public. The results obtained were very positive and rewarding, as it can be verified through the responses of 23 teachers to an evaluative questionnaire available on the website. We observed the great use of Digital Didactic Materials by English Language teachers from different places, their satisfaction and positive impression in relation to the material, as well as the great acceptance among sixth year students.